2020
DOI: 10.3389/fonc.2020.01412
|View full text |Cite
|
Sign up to set email alerts
|

The Preferred Locations of Meningioma According to Different Biological Characteristics Based on Voxel-Wise Analysis

Abstract: Objective: Meningiomas presented preferred intracranial distribution, which may reflect potential biological natures. This study aimed to analyze the preferred locations of meningioma according to different biological characteristics. Method: A total of 1,107 patients pathologically diagnosed with meningiomas between January 2012 and December 2016 were retrospectively analyzed. Preoperative MRI were normalized, and lesions were semiautomatically segmented. The stereospecific frequency and p value heatmaps were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 32 publications
(52 reference statements)
5
34
3
Order By: Relevance
“…In contrast to some studies where high grade meningiomas more frequently were found over the convexity [11,23,33,42] and non-skull base regions [18,39], we found no such association between WHO grade and tumor locations. In our population based selection the overall median tumor volume was 6.1 cm 3 (mean 16.8 cm 3 ), which is somewhat larger than in reports of incidentally discovered and surgically treated meningiomas [12,27,8,23].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to some studies where high grade meningiomas more frequently were found over the convexity [11,23,33,42] and non-skull base regions [18,39], we found no such association between WHO grade and tumor locations. In our population based selection the overall median tumor volume was 6.1 cm 3 (mean 16.8 cm 3 ), which is somewhat larger than in reports of incidentally discovered and surgically treated meningiomas [12,27,8,23].…”
Section: Discussioncontrasting
confidence: 99%
“…We found a higher frequency in females, with a female-male ratio of 3:1 to 2:1, slightly higher than other studies [2,[4][5]. We also found that meningiomas are more frequent in the supratentorial compartment, with about 90% of occurrences, especially in the lateral skull, which has been a constant finding in several studies [4][5]7,13,[23][24][25][26]. In this study, 25 of 32 meningiomas (78%) were PR positive and more frequent in women (72%, n=18/25).…”
Section: Discussionsupporting
confidence: 66%
“…The notable advantage of voxel-wise approach is registering the MRI to a standard brain template (e.g., MNI152) for normalization, realizing the transformation of specific voxels to corresponding coordinates, which is immune to the MRI field strength [ 23 ]. Our previous work showed the preferred locations of meningiomas using the voxel-wise analysis [ 24 ]. Therefore, the voxel-wise approach could be useful to unfold the heterogenetic localization of BMs.…”
Section: Discussionmentioning
confidence: 99%